Selecting array configurations for MIMO systems an evolutionary computation approach. - Karamalis, P.D (IEEE Transactions on wireless communications)
This paper presents an antenna selection method for multiple-input multiple-output wireless systems. By exploitation of the channel transfer matrix, the antenna selection criterion is the maximization of the instantaneous capacity achieved using a specific number of transmitting and receiving antenna array elements. For each environment, the proposed method applies a genetic algorithm which seeks the most advantageous subset of antenna elements. The results are based on measured and simulated channels and show that the proposed method selects array configurations that yield superior performance compared to the arrays usually employed. Furthermore, comparative analysis results are presented, with respect to a state-of-the-art algorithm.